Teacher Contribution as Learning Agent at SMP Negeri 32 Pekanbaru - Angel Cristina; Erni (RETORIKA: Jurnal Ilmu Bahasa, 2023)
Education is a process in the form of learning and teaching activities which basically has the aim of equipping students to be able to have the ability to interact and master the knowledge that has been taught. Teachers play a role and become a factor that greatly determines the smoothness and running of an education, because all learning activities are the centre of the entire educational process. The purpose of this research is to find out the role of teachers as learning agents at SMP Negeri 32 Pekanbaru. This research uses descriptive qualitative method with the research subjects are teachers at SMP Negeri 32 Pekanbaru as many as 11 people. Data collection techniques in this study were obtained through interviews, observation and documentation. The results showed various perceptions of teachers who were able to provide a good learning agent role for students, such as the role of the teacher as a facilitator, the role of the teacher as a motivator, the role of the teacher as a driver of learning, the role of the teacher as a learning engineer, and the role of the teacher as an inspirer, and teachers were able to identify some of the potential of students related to the lessons taught, learning problems that they like, teaching subjects by giving re-evaluation before starting learning in the classroom.